Plant Nutrient Availability in Soils of Rice Root Zone and Root Free Areas under Different Management Practices - Khan, Md. Asaduzzaman; Shampa, Selina Aktar; Hossain, Md. Baktear (Journal of the Bangladesh Agricultural University, 2024)
The availability of nutrients in soils is dependent on a number of factors including the sources of the nutrient, moisture level and soil properties. The objective of this study was to determine the effects of irrigation, fertilizer and manure on nutrient availability in rice root zone and root free areas. The experiment was laid out in split plot design with a distribution of irrigation (I1: continuous flooding and I2: saturated condition) to the main plots and fertilizers to the sub plots. The fertilizer treatments were T0: Control, T1 =100% RDCF, T2 =50% RDCF + 5 t ha-1 cowdung, T3:70% RDCF + 3 t ha-1 cowdung, T4: 50% RDCF + 5 t ha-1 compost, T5: 70% RDCF + 3 t ha-1 compost, T6: 50% RDCF + 3.5 t ha-1 poultry manure, T7: 70% RDCF + 2.1 t ha-1 poultry manure. A PVC core was installed up to 40 cm depth in the middle of each plot and rice was not grown into the core but treatments were applied similar to the rice growing area and pore-water samples were collected from rice root zone and root free areas and analyzed. There was a positive correlation between rice yield and pore-water K or P of flowering stage. The higher pore-water nutrients and grain yields were obtained from organic plus inorganic fertilizer treatments. The 3 to 4 fold higher levels of pore-water K concentrations, 1.4 to 3 fold higher soil exchangeable K and 1.5 to 2 times soil available P were found in the soils of root free area than root zone area. The higher levels of soil organic matter, N, P and K were obtained in inorganic plus organic fertilizer treatments of root zone and root free areas and available P, K concentrations were highly increased in the soils of root free areas. J Bangladesh Agril Univ 19(1): 44–52, 2021 https://doi.org/10.5455/JBAU.36895